2021
DOI: 10.3390/s21217012
|View full text |Cite
|
Sign up to set email alerts
|

Development of Low-Frequency Phased Array for Imaging Defects in Concrete Structures

Abstract: The nondestructive inspection of concrete structures is indispensable for ensuring the safety and reliability of aging infrastructures. Ultrasonic waves having a frequency of tens of kHz are frequently used to reduce the scattering attenuation due to coarse aggregates. Such low frequencies enable the measurement of the thickness of concrete structures and detection of layer-type defects, such as delamination, whereas it causes a lack of sensitivity to crack-type defects. In this paper, to realize the ultrasoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The nondestructive inspection of concrete structures is indispensable for ensuring the safety and reliability of aging infrastructures. Ultrasonic waves having a frequency of tens of kHz are frequently used to reduce the scattering attenuation due to coarse aggregates (Ohara et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The nondestructive inspection of concrete structures is indispensable for ensuring the safety and reliability of aging infrastructures. Ultrasonic waves having a frequency of tens of kHz are frequently used to reduce the scattering attenuation due to coarse aggregates (Ohara et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aldo et al [3] applied ultrasonic phased arrays to concrete inspection and demonstrated that the technique could detect in a dry coupled state and still identify defects in the presence of reinforcement. Ohara et al [4] applied an array transducer to a concrete specimen with delamination, and the PA with the LF array transducer clearly visualized the delamination. Therefore, phased array ultrasonic technology can be considered an effective means of detecting the quality of tunnel grouting, and the key to realizing this technology lies in two aspects: phased array optimization and signal noise reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Most UT employs piezoelectric transducers. Among them, the ultrasonic phased array, using a piezoelectric array transducer, has been intensively studied for visualizing internal [8][9][10][11][12][13][14][15][16] and surface defects. [17][18][19] Additionally, various types of UT using laser scanning, have also been studied.…”
Section: Introductionmentioning
confidence: 99%